2008
DOI: 10.1159/000185548
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Egr-1 Antisense Oligodeoxyribonucleotide on Myocardial Injury Induced by Ischemia-reperfusion and Hypoxia-reoxygenation

Abstract: Aims: Our previous studies have shown that myocardial ischemia-reperfusion (I/R) injury is related closely with early growth response (Egr)-1 overexpression. The present study is to confirm thoroughly the effects of Egr-1 on the occurrance and development of myocardial I/R injury. Methods: The Sprague-Dawley rat myocardial I/R model and cultured cardiomyocyte hypoxia-reoxygenation (H/R) model were established. The synthesized Egr-1 antisense oligodeoxyribonucleotide (AS-ODN) was transfected into myocardial tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…Egr-1 has a well-established pivotal role in the pathogenesis of lung I/ R injury [8,15]. Furthermore, our previous study also confirmed that Egr-1 might play a vital role in the pathogenesis of myocardial I/R injury [18].…”
Section: Introductionsupporting
confidence: 76%
“…Egr-1 has a well-established pivotal role in the pathogenesis of lung I/ R injury [8,15]. Furthermore, our previous study also confirmed that Egr-1 might play a vital role in the pathogenesis of myocardial I/R injury [18].…”
Section: Introductionsupporting
confidence: 76%
“…Lo et al employed bovine aortic endothelial cells with hypoxia and found that Egr-1 mRNA expression rapidly increased within 30 minutes [9]. These results showed that Egr-1 expression of endothelial cells occurs more quickly than that of cardiomyocytes, which noticeably begins at 1 hour after reperfusion [13,16]. According to the recent data, levels of Egr-1 expression are upregulated in various organs including the heart [24], lung [3,25], gut [26] and kidney [27] after I/R challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence of antisense Egr-1 ODN was 3'-TAC CGT CGC CGG TTC -5' as described previously [16]. For control experiments, scrambled-sequence Egr-1 ODNs (3'-TCG TGC CGC TGC CAT -5') were used [1].…”
Section: Preparation Of Antisense and Scrambled-sequence Egr-1 Oligodmentioning
confidence: 99%
“…Ca 2+ overload during reperfusion may occur by several mechanisms. One mechanism is related to increased Ca 2+ influx through 18 Ca 2+ channels. The second mechanism is the reduced Ca 2+ reuptake by the sarcoplasmatic reticulum.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that the overexpression of Egr-1 could be the common denominator in ischemia/reperfusion injury in various organs, so it might be a good therapeutic target in ischemia/ reperfusion conditions. Our previous study involving antisense Egr-1 oligodeoxyribonucleotides suggested that overexpression of Egr-1 was a causal factor in myocardial ischemia/reperfusion or hypoxia/reoxygenation injury, and F 2 could protect myocardial tissues and cells against ischemia/reperfusion or hypoxia/reoxygenation injury, which was largely due to the inhibition of Egr-1 overexpresssion [17,18].…”
Section: Introductionmentioning
confidence: 99%